Preparation and barrier properties of SPEEK/Cloisite 15A®/TAP nanocomposite membrane for DMFC application - Jaafar, Jafariah (Elsevier BV, 2009)
Sulfonated poly (ether ether ketone) (SPEEK)/Cloisite 15A® nanocomposite membranes were fabricated by incorporating 2,4,6-triaminopyrimidine (TAP) as compatiblizer and characterized for DMFC application. The SPEEK-nanocomposite membranes were prepared via solution intercalation method. The membranes were then characterized based on their thermal and physical properties as a function of Cloisite 15A® and TAP loading. The characteristics of the SPEEK nanocomposite membranes were then compared with the parent SPEEK membrane and the commercially available Nafion 112 membrane. The XRD confirmed that intercalation took place in the SPEEK nanocomposite membranes. The membrane stability, i.e. the liquid uptake in water and in the aqueous methanol solution, as well as the mechanical and thermal stability significantly were improved with the Cloisite 15A® and TAP loadings into the SPEEK polymer matrix. The barrier performance of SPEEK/Cloisite 15A®/TAP was significantly enhanced to compete with the expensive Nafion 112 membrane. Higher proton conductivity of 3.87 × 10-3 S cm-1, which is higher than that of the parent SPEEK membrane, was also attained.